Biomolecular modelling of the intrinsically disordered proteins in liquid-liquid phase separation - Hu, Zixin (Nanyang Technological University, 2025)
Liquid-liquid phase separation (LLPS) is of significant biological importance and is widely reported in many biological systems. Intrinsically disordered proteins or regions (IDP/Rs) are a class of proteins or regions that lack well-folded structures and are thought to be a major driving force of LLPS. This thesis studied the function of IDP/Rs in biomolecular LLPS systems with computational tools, mainly molecular simulation. It contains three parts. First, it studied the role of IDRs in fine-tuning the oligomerization of Coronin, which is important in regulating actin polymerization. Second, it developed a new coarse-grained (CG) model with refined bonded potentials to improve the backbone conformation of IDP/Rs. Third, it explored the multivalency of IDPs in a customized LLPS database to have a deeper insight into LLPS propensity. Collectively, this thesis provided a more accurate computational tool to study IDP/Rs and contributed to understanding the functions of IDP/Rs and the nature of LLPS.